Guaiac faecal occult blood screening in individuals younger than 50 years of age. Issue 3 (May 2017) - Zalts, Ronen; Moadi, Zeid; Avizohar, Ophir; Leiba, Ronit; Half, Elizabeth; Karban, Amir
Abstract : To determine the effectiveness of guaiac faecal occult blood tests (gFOBT) in the early detection of colorectal cancer (CRC) within a population of asymptomatic individuals who attended general periodic examinations, and to suggest the recommended age for this screening tool, the electronic database of the periodic examination institute of Rambam Healthcare Campus for the years 2004–2013 was reviewed. Individuals with positive gFOBT results were interviewed for further workup. Proportions of individuals for whom a polyp or CRC was detected were evaluated according to sex and age. 18 858 individuals were examined during the study period, mean age 48 years. The overall gFOBT uptake was 40.8%. Uptake was significantly higher among men and increased with age. Positive gFOBT was detected in 105 individuals (1.4%). The proportion of positive gFOBT was significantly lower among individuals aged 30–50 years than those older than 50 years of age (1.1 and 1.7%, respectively, P =0.005). No positive gFOBT was detected among individuals younger than 30 years of age. Positive gFOBT was higher in men than in women: 1.8 and 0.9% respectively ( P =0.002). CRC was detected in six individuals, including two younger than 50 years of age. Polyps were detected in 15 individuals; of these, four were younger than 50 years of age. In the gFOBT-positive group, proportions of polyps and CRC were the same for subgroups according to age. The findings support consideration of annual gFOBT screening from the age of 40 years.